2009
DOI: 10.1074/jbc.c900014200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of ROCK1 Causes Insulin Resistance in Vivo

Abstract: Insulin signaling is essential for normal glucose homeostasis. Rho-kinase (ROCK) isoforms have been shown to participate in insulin signaling and glucose metabolism in cultured cell lines. To investigate the physiological role of ROCK1 in the regulation of whole body glucose homeostasis and insulin sensitivity in vivo, we studied mice with global disruption of ROCK1. Here we show that, at 16 -18 weeks of age, ROCK1-deficient mice exhibited insulin resistance, as revealed by the failure of blood glucose levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
127
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 37 publications
9
127
1
1
Order By: Relevance
“…Studies in cultured cells have suggested that both ROCK isoforms promote Ser 632/635 phosphorylation of IRS, although the consequences on downstream insulin signaling seem to vary in different cell types (14,30). Furthermore, the genetic deletion of ROCK1 resulted in decreased Ser 632/635 phosphorylation of IRS in skeletal muscle, which was associated with reduced Tyr 612 phosphorylation and insulin signaling (21). However, in the present study, the reduced Tyr 612 phosphorylation of IRS was not associated with a change in Ser 632/635 phosphorylation in hearts from HFD-WT mice, despite increases in the activity of ROCK1 and ROCK2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cultured cells have suggested that both ROCK isoforms promote Ser 632/635 phosphorylation of IRS, although the consequences on downstream insulin signaling seem to vary in different cell types (14,30). Furthermore, the genetic deletion of ROCK1 resulted in decreased Ser 632/635 phosphorylation of IRS in skeletal muscle, which was associated with reduced Tyr 612 phosphorylation and insulin signaling (21). However, in the present study, the reduced Tyr 612 phosphorylation of IRS was not associated with a change in Ser 632/635 phosphorylation in hearts from HFD-WT mice, despite increases in the activity of ROCK1 and ROCK2.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ROCK1 is required for normal insulin sensitivity in mice, since its deletion was associated with reduced tyrosine phosphorylation of IRS and impaired glucose transport in skeletal muscle (21). However, recently, ROCK1 was also shown to negatively regulate insulin signaling in adipose tissue (23).…”
mentioning
confidence: 99%
“…Insulin signaling is essential for normal glucose homeostasis. ROCK1 have been demonstrated as a novel regulator of glucose homeostasis and insulin sensitivity in vivo [43] . However, studies of the effects of ROCK inhibitors on glucose metabolism in vivo have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and co-workers (29,30) have reported that inhibition of the Rho kinase isoform Rock1 causes insulin resistance in skeletal muscle via inhibitory phosphorylation of IRS-1 and decreases downstream signaling, whereas Bankar's study (31) finds that heterozygous Rock2 deficiency augments skeletal muscle IRS-1/PI3K/Akt signaling and whole body insulin sen- sitivity. These studies indicate that the role of Rock2 in regulation of insulin sensitivity is opposite to that of Rock1.…”
Section: Discussionmentioning
confidence: 99%